Relações entre o tempo atmosférico e doenças cardiorespiratórias na cidade de Cordeirópolis-SP - Genaro, Vinicius [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Cordeirópolis é uma cidade com aproximadamente 20.000, localizada em meio a Depressão Periférica Paulista, uma das regiões com umidade relativa do ar mais baixas do estado de São Paulo durante a estação de inverno. Por outro lado, a cidade também conta com uma série de problemas socioambientais, como a exploração indiscriminada dos recursos naturais e os baixos níveis educacionais apresentados pela população local, colocando em risco a qualidade de vida dos habitantes. Diante dos fatos, buscou-se estabelecer relações entre os diferentes tipos de tempo atmosférico e as doenças cardiorrespiratórias, considerando que as variações do tempo atmosférico tendem a desencadear uma série de reações no organismo humano, causando ou agravando um emaranhado de sintomas, enfermidades e mudanças no quadro clínico de saúde da população. Também foi possível identificar os grupos de risco e mapear as áreas mais vulneráveis e o local de residência dos pacientes portadores de enfermidades ligadas ao sistema circulatório e respiratório atendidos pelo Programa Saúde da Família, servindo de contribuição para que o poder público possa pensar novas diretrizes que sejam ecologicamente, social e economicamente mais viáveis e justas

Cordeirópolis is a small town with approximately 20,000 inhabitants and is located in the midst of the Depressão Periférica Paulista, one of the driest regions of the state of São Paulo during the winter season. On the other hand, the city is among the largest and most important deposits of clay, which explains its economic vocation, aimed mainly to the production of ceramic artifacts and agriculture of sugar cane. Despite being part of the largest ceramic center in Latin America,and although the ceramic industries as well as the sugar industry are the main sources of income of the municipality, the city has a number of socio-environmental problems, such as the indiscriminate exploitation of natural resources and low levels of education provided by the local population, threatening the quality of life for residents. Given the above facts, we sought to establish relationships between different types of weather and cardiopulmonary diseases, considering that variations in the weather tend to trigger a series of reactions in the human body, causing or exacerbating a tangle of symptoms, diseases changes in clinical and population health. By the way, were collected, processed and organized weather data on precipitation, temperature, relative humidity and air quality standard, and was then correlated with the information collected by the Hospital Health System (SIH-SUS), referring to the monthly number of patients hospitalized for some kind of cardiopulmonary disease. Through the questionnaires it was possible to identify risk groups and map the area’s most vulnerable and place of residence of patients with diseases related to circulatory and respiratory system served by the Family Health Program, serving as a contribution to the local government can think of new guidelines that are environmentally, socially and economically more viable and fair
Keywords: Geografia medica; Bioclimatologia; Saude ambiental - Pesquisa - Cordeirópolis (SP); Climatologia medica - Cordeirópolis (SP); Medical geography; Bioclimatology; Environmental health - Research; Medical climatology